Cultures of disaster : society and natural hazards in the Philippines - Bankoff, Greg (RoutledgeCurzon, 2003)
Explores the relationship between environment and culture in the contemporary Philippines. The book will be of interest to those engaged in relief policy and administration in developing countries.